Antioxidant and Antibacterial Activity of Bioactive Compound Produced By Endophytic Fungi - Olaleye, O. N.; Omotayo, M. A.; Avungbeto, M. O.; Olojede, O. S.; Lawal, D. B.; Adeola, O. B. (European Journal of Applied Sciences, 2022)
The present study aims evaluated the antibacterial and antioxidant activity of bioactive compounds synthesized by endophytic fungi obtained from Anacardium occidentale (AO), Terminalia cattappa (TC) and Sygygium jambos (SJ). The compounds produced by the isolated endophytic fungi from the medicinal plants used in this study were extracted with ethylacetate and subjected to antioxidant and antibactrerial activities using standard procedures. Screened for bioactivity using the disc diffusion method. Five fungal species were isolated from the plants and were identified to be Aspergillus terreus, Cladosporium spp, Mucor racemosus, Aspergillus oryzae, F. oxysporum. Alkaloids, saponins and steroids were detected in all the extracts while tannin and phenols were not detected. However, flavonoids was detected in SJ1 and TC2 only. All the extracts obtained from this study showed good antioxidant activity with SJ1 having the highest DPPH radical scavenging compared to the other extracts. All the extracts inhibited the growth of both E. coli and S. aureus with a range of 10-35 mm in diameter. The MBC: MIC of AO, SJ1 and SJ2 was 2.0 for both S. aureus and E. coli while that of TC2 was 10. In conclusion, the compounds produced by the isolated fungi possess both antioxidant and antibacterial activity which can be used for development of new drugs.